The impact of the hydrological condition of Kashkadarya oasis on the formation of agrolandscapes - Suyunov Abdusali; Aminjanova Malika; Khushmurodov Farrukh; Usmanova Rokhatjon; Erdonov Latif; Mukumova Husnora; Navotova Dilnoza; Sultanov Shukhrat (E3S Web of Conferences, 2024)
The article discusses the hydrological condition of Kashkadarya province, rational use of land resources and factors contributing to the degradation of agroirrigation landscapes due to soil erosion. It also highlights the impact of surface and groundwater on the socio-economic development of the region, as well as geographical and environmental issues of land use in the process of intercropping.